Connecting to Compete 2007 : Trade Logistics in the Global Economy--The Logistics Performance Index and Its Indicators - Arvis, Jean-Francois; Alina Mustra, Monica; Panzer, John; Ojala, Lauri; Naula, Tapio (World Bank, Washington, DC, 2016)
This is the first report presenting the Logistics Performance Index (LPI) and indicators. It aims to shed light on how different countries are doing in the area of trade logistics, and what they can do to improve their performance. It is based on a worldwide survey of the global freight forwarders and express carriers who are the most active in international trade. LPI and its underlying indicators constitute a unique dataset to measure country performance across several dimensions of logistics and to benchmark that logistics performance against 150 countries. It provides the empirical basis to understand and compare differences in trade logistics as well as to inform policy with respect to difficult bottlenecks and tradeoffs. As a tool for policymakers, professionals, development agencies, and other stakeholders, it will directly support the fast-growing agenda for reforms and investments in trade and transport facilitation. The report provides some insights on the cost of poor logistics to country competitiveness and the sources of those higher costs. Beyond cost and time taken to deliver goods, the predictability and reliability of supply chains is increasingly important in a world of just-in-time production sharing. Costs related to hedging against uncertainty are significant. Equally, cost and quality of logistics are determined not just by infrastructure and the performance of public agencies, but also by the availability of quality and competitive private services. Moreover, in many developing countries, problems of adverse geography are compounded by a weak modern services sector due to poor institutions or over-regulation. The report closes with some practical insights, advocating a comprehensive, integrated approach to ensure that actions in one area are not rendered ineffective by bottlenecks in another.